Transfer zapornikov znotraj EU - res v imenu socialne reintegracije? - Ambrož, Matjaž (Revija za kriminalistiko in kriminologijo, 2012)
The transfer of the enforcement of sentences between states raises many penological, legal, political and financial questions. The traditional system of transfer based on tripartite consent (consent of the state of the judgement, the state of enforcement and state of the convict) is undergoing change: instead, a system allowing transfer against the will of the convict is being introduced, which requires states to enforce the sentence imposed on their citizens by foreign courts, in some cases even without verifying dual criminality. At the EU level, these changes are being justified by the provision of the optimum opportunities for social rehabilitation (resocialisation) of the convict; however, much more mundane reasons lie behind this justification: countries with a high percentage of foreigners in their prison populations would like to be partly relieved of this burden, quickly and without administrative complications, if possible. In numerous cases, the transfer of convicts to serve sentences in their country of origin is in the prisoners' interests, but not invariably (e.g. worse living conditions in the prisons of the country to which they have been transfer red,longer waits for probation). Therefore, shifts in the field of transfer can be seen, at least from one perspective, as sacrificing the convicts' position on the altar of the rhetoric of mutual recognition of judicial decisions and the provision of optimum opportunities for the resocialisation of convicts.
Keywords: dual criminality; dvojna kaznivost; enforcement of sentences; EU; Evropska unija; izvrševanje kazenskih sankcij; obsojenci; pogojni odpust; probation; resocialisation; resocializacija; transfer obsojencev; transfer of convicts